Cannabidiol oil in the treatment of super refractory status epilepticus. A case report. (February 2016) - Rosemergy, Ian; Adler, Jonathan; Psirides, Alex
Highlights: Cannabidiol (CBD) was used in convulsive status epilepticus and was not effective. Portrayal of benefits of CBD in main stream and social media was often unrealistic. Ethics committee was useful in negotiating a treatment pathway involving CBD.